Fiber reinforced composite material with strain-damage self-sensing function and preparation method thereof
By embedded thermoplastic film and dopamine activation modification on the surface of the fiber composite material, combined with nanomaterials, a three-dimensional conductive path is formed, which solves the problem of insufficient self-perception ability of fiber composite materials, and achieves efficient damage monitoring and material self-healing. Extend material life and reduce preparation costs.
Patent Information
- Application Number
- CN202411308383.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-10
AI Technical Summary
Existing fiber composites are insufficient in harsh service environments, resulting in structural service reliability and life problems. In the prior art, the conductivity of fiber surface conductivity is not conducive to damage perception, the synergistic effect between additives is unclear, and the operation is complicated. And it is costly.
By inserting thermoplastic film on the surface of the thermoset composite material, welded connection and desoldering and dissociation are achieved bidirectionally reversible, and the modified fiber surface is activated by dopamine, combining hydroxylated multi-walled carbon nanotubes and nanotitanium dioxide to form a three-dimensional conductive path to perceive damage .
The strain-damage self-perception function of fiber-reinforced composite materials is realized, the damage monitoring sensitivity and the mechanical toughness of the material are improved, the service life of resin-based composite materials is extended, and the intelligent self-healing function is given, which simplifies the preparation process and Reduced costs.
Smart Images

Figure CN119286190A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fiber-reinforced resin-based composite materials, and in particular to a fiber-reinforced composite material with strain-damage self-sensing and a preparation method thereof. Background Art
[0002] Fiber reinforced polymer (FRP) composites have the advantages of light weight, high strength, corrosion resistance, and fatigue resistance. In recent years, they have been widely used in aerospace, marine energy, civil engineering and other fields. FRP is composed of a fiber reinforcement phase, a resin matrix connection phase and a fiber / resin interface. The fiber acts as a mechanical skeleton and determines the mechanical properties of the composite material; the resin matrix connects and fixes the fibers in the composite material to ensure that the fibers are subjected to force synchronously; the fiber / resin interface, as the transition area between the fiber and the resin, mainly plays a stress transfer role to ensure the deformation coordination of the fiber and the resin.
[0003] However, during the service of FRP, the fiber and epoxy resin matrix deform asynchronously, resulting in defects in the fiber-resin interface and the resin matrix, and various damages (such as fiber breakage, fiber / resin interface debonding, resin matrix cracking, etc.). In addition, compared with carbon fiber, the epoxy resin matrix is brittle and easy to crack, and has poor impact resistance and weather resistance, resulting in interface debonding or matrix cracking before the fiber breaks. The micro-scale damage will gradually expand, causing the material to suddenly fail macroscopically, seriously affecting the service reliability, safety and service life of the structure. Therefore, how to achieve self-sensing of damage in FRP under harsh service environments and complex load conditions, and monitor the service coordination of its internal fibers and resins, is a huge challenge facing the safe, reliable and long-life service of FRP engineering structures.
[0004] In the prior art, CN117264401B discloses a method for preparing a basalt fiber composite material with self-sensing damage and temperature-sensitive behavior, by grafting carbon nanotubes and reduced graphene oxide on the surface of basalt fiber, and using a single-screw extruder to extrude the filament, and using 3D printing to make a basalt fiber composite material with electrical properties, and at the same time giving the composite material a self-sensing damage function. CN116515274B discloses a method for preparing a basalt fiber composite material with self-sensing damage ability, by depositing conductive fillers on the surface of basalt fiber through electrostatic self-assembly, increasing its surface roughness, improving the mechanical and electrical properties of the composite material, and giving the composite material a self-sensing damage function.
[0005] CN114414107B discloses a high-strength carbon fiber composite material with self-sensing function and a preparation method. A piezoelectric nanolayer of barium titanate material is loaded on the carbon fiber woven layer, and is plated on the surface of the carbon fiber woven layer layer by layer in the form of a single atomic film. Therefore, the deposited crystal layer has extremely uniform thickness and excellent consistency. Through selective deposition through a mask, the morphology and array distribution of the subsequent piezoelectric nanolayer can be accurately controlled, and finally the material can detect sensitive and considerable piezoelectric signals.
[0006] However, the above patented fiber composite material damage self-sensing system realizes the self-sensing technology of in-situ damage of composite materials through resistance change, which is low in maturity and faces theoretical and technical bottlenecks such as a series of material functional design and damage accuracy judgment; in addition, the existing fiber composite material self-sensing technology has problems such as feasibility and applicability, and how to realize actual structural application still has a series of scientific and technical difficulties. Further, the research goal of the fiber surface conductive treatment in the above patent is to improve the interface conductivity and interface bonding strength. For example, the fiber surface grafted with nano-conductive particles can greatly improve the conductivity and interface bonding performance of the interface. However, the high conductivity of the interface layer is not conducive to sensing the damage of the interface through resistance change. For example, the partial debonding of the fiber and the resin cannot effectively destroy the conductive channel of the high conductivity interface, which will lead to the interface damage not causing a significant change in resistance, and the sensitivity of damage perception is reduced. Finally, the self-sensing function division between the above additives is unclear and cannot play a good synergistic effect. At the same time, it lacks micro-regulation and systematization, and has different disadvantages such as complex operation, unclear self-sensing effect, high cost, low process efficiency, and frequent accidents during use. Summary of the invention
[0007] The technical problem to be solved by the present invention is: in view of the technical problems existing in the prior art, the present invention provides a fiber-reinforced composite material with strain-damage self-sensing and a preparation method thereof, and realizes bidirectional reversibility of welding connection and desoldering dissociation of thermosetting composite materials by embedding a thermoplastic plastic film on the surface of the thermosetting composite material.
[0008] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0009] A fiber-reinforced composite material with strain-damage self-sensing comprises the following raw material components in parts by weight:
[0010] 0.1-0.5 parts dopamine;
[0011] 0.1 to 1 part of carboxylated multi-walled carbon nanotubes;
[0012] 3-5 parts of nano titanium dioxide;
[0013] 20-60 parts of acetone;
[0014] 20-80 parts of anhydrous ethanol;
[0015] 80-120 parts of deionized water;
[0016] 1-10 parts of polyethylene glycol;
[0017] 0.1-2 parts of ammonia water;
[0018] 0.1-1 part of polyvinyl pyrrolidone;
[0019] 1 to 3 parts of silane coupling agent;
[0020] 60-80 parts of unidirectional fiber cloth;
[0021] 1-5 parts of polycaprolactone;
[0022] 80-120 parts of epoxy resin and corresponding amount of curing agent.
[0023] As a further improvement of the above technical solution:
[0024] In the above technical solution, preferably, the reinforcing phase fiber is one of carbon fiber, glass fiber, basalt fiber and plant fiber.
[0025] In the above technical solution, preferably, the carbon fiber is pretreated before use, and the pretreatment is first desizing and then acidifying the desizing carbon fiber.
[0026] Preferably, in the above technical solution, the basalt fiber is pretreated before use, and the pretreatment is first plasma oxidation treatment to carboxylate or hydroxylate the fiber surface.
[0027] In the above technical scheme, preferably, the dopamine is composed of amino groups and phenolic hydroxyl groups, and is easily dissolved and oxidized in a weakly alkaline aqueous solution to induce a self-polymerization cross-linking reaction to form a polydopamine coating rich in catechol groups, and is evenly attached to the fiber surface to improve the fiber surface roughness and chemical activity, especially for inert carbon fibers, which can significantly improve the fiber-resin interface bonding performance, facilitate the uniform transfer of external loads to the fibers and resin, and give full play to the coordination between the fibers and the resin in the fiber-reinforced composite material.
[0028] Preferably, in the above technical solution, the hydroxylated carbon nanotubes have a diameter of 8 nanometers to 50 nanometers and a length of 10 micrometers to 50 micrometers.
[0029] Preferably, in the above technical solution, the particle size of the nano titanium dioxide is 30-100 nanometers.
[0030] The present invention also provides a method for preparing a fiber-reinforced composite material with strain-damage self-sensing, comprising the following steps:
[0031] Step S1: Surface activation modification of carbon fiber based on dopamine;
[0032] Prepare a mixed solution of ethanol and deionized water, add different volumes of ammonia water dropwise, and stir evenly to obtain a mixed solution A; add dopamine and polyethylene glycol to the deionized water in sequence, stir evenly, then add them to the mixed solution A respectively, and stir evenly at room temperature to obtain a mixed solution B; place the fiber cloth in the mixed solution B at 60°C until the fiber surface is evenly covered, take out the fiber cloth after immersion, and dry it for standby use;
[0033] Step S2: preparing an epoxy resin solution having damage self-sensing function;
[0034] The following steps are involved:
[0035] S2-1, adding polycaprolactone to acetone, heating and stirring at a temperature of 30-50°C for 20-40 minutes to dissolve, then adding nano titanium dioxide, stirring for 20-40 minutes to obtain solution I;
[0036] The polycaprolactone is incorporated into the resin matrix as a low-melting-point thermoplastic small molecule, and after heating and melting, the melt diffuses into the crack area to fill the internal pores and other defects of the epoxy resin, thereby improving the fracture toughness of the resin system; in addition, the molecular chains of the thermoplastic polycaprolactone melt will be entangled with each other at the thermal activation temperature, and bonded with the resin matrix, showing good interface adhesion;
[0037] S2-2, adding carboxylated multi-walled carbon nanotubes, silane coupling agent and polyvinylpyrrolidone into anhydrous ethanol solution to obtain solution II;
[0038] S2-3, adding solution I to solution II, stirring for 30-60 minutes to obtain solution III, then adding solution III to epoxy resin, stirring evenly to obtain solution IV, then placing solution IV in an 80-120°C oil bath, heating and stirring for 4-6 hours until the solvent evaporates to obtain solution V, and then adding a curing agent to obtain epoxy resin solution VI with damage self-sensing function;
[0039] The solution III is a suspension uniformly dispersed in ethanol, and its dispersion mechanism is that the silicon in the silane coupling agent forms a silicon-oxygen covalent bond with the oxygen in the hydroxylated carbon nanotubes; at the same time, the amino group in the silane coupling agent dehydrogenates / waters with the hydroxyl or carboxyl group on the surface of the pretreated fiber to form a NO or NC covalent bond, thereby improving the surface activity, mechanical properties and roughness of the fiber;
[0040] Step S3: designing a fiber-reinforced composite material with strain-damage self-sensing;
[0041] The epoxy resin solution VI of step S2 and the fiber cloth modified in step S1 are vacuum infused to obtain a fiber reinforced composite material plate having strain-damage self-sensing functional characteristics, and then cured in an oven at 60° C. for 48 hours.
[0042] The internal current of the composite material prepared by the vacuum infusion process can be transmitted through the contact of the conductive fillers to achieve the conductivity of the material. At the same time, the material strain or internal damage will affect the conductive path inside the fiber composite material, resulting in a change in resistivity. Therefore, by monitoring the resistivity of the fiber composite material, its strain or small internal damage can be sensed, realizing the self-sensing function of internal damage of the fiber reinforced composite material.
[0043] Fiber-reinforced composites are composed of a fiber reinforcement phase, a resin matrix connecting phase, and a fiber / resin interface. Compared with the fiber, the resin matrix and the interface are relatively weak, and microcracks are preferentially initiated and extended. Therefore, it is particularly important to strengthen the resin matrix and modify the fiber interface. Therefore, dopamine-based fiber activation modification is used to enhance the interfacial bonding with the resin matrix; at the same time, the crack pinning and blocking effect of nano-titanium dioxide particles and the high elongation of polycaprolactone are used to improve the fracture toughness of the resin matrix, and the high strength and high modulus of carbon nanotubes are used to improve the mechanical properties of fiber-resin composites.
[0044] The fiber-reinforced composite material with strain-damage self-sensing and the preparation method thereof provided by the present invention have the following advantages compared with the prior art:
[0045] The fiber-reinforced composite material with strain-damage self-sensing of the present invention and its preparation method, through the synergistic effect between functional particles, based on dopamine activation modification to improve fiber-resin interface bonding performance and nano-titanium dioxide toughened epoxy resin matrix (crack pinning, blocking effect), using the high electrical conductivity and heat transfer characteristics of multi-walled carbon nanotubes, so that the fiber-reinforced composite material can sense the occurrence and development of damage by resistance change, and achieve real-time monitoring of damage, and can deeply understand the relationship between damage and resistance change, giving the composite material self-sensing function. When the composite material produces a large strain and the corresponding system internal resistance suddenly changes, the low melting point polycaprolactone small molecule melt after heating and melting will diffuse the crack area to achieve the filling of defects such as internal pores of epoxy resin, which is convenient to improve the fracture toughness of the resin system. At the same time, the polycaprolactone melt molecular chain will be entangled with each other at the thermal activation temperature, and bonded with the resin matrix, showing good interface adhesion. Among them, the premise of giving the composite material the strain-damage self-sensing function is that the conductive reinforcing and toughening fillers (multi-walled carbon nanotubes, nano-titanium dioxide) need to be evenly dispersed in the resin matrix and at its interface with the fiber, and form a three-dimensional conductive path to improve the damage perception sensitivity of the fiber-reinforced resin-based composite material.
[0046] The fiber-reinforced composite material with strain-damage self-sensing and the preparation method thereof of the present invention have a very small amount of additives in the reinforced modified composite material, while ensuring that the composite material has excellent mechanical toughness and a three-dimensional conductive network structure, achieving a low additive content and giving the composite material excellent mechanical strength and fracture toughness. At the same time, when the fiber-reinforced composite material system produces defects such as fiber breakage, resin cracking, and interface debonding, the composite material internal damage self-sensing function is realized according to the influence of the internal damage of the material on the conductive network (i.e., resistance), that is, the real-time service status of the composite material under complex stress and wet-heat aging coupling conditions can be inspected / monitored, and the damage location inside the material can be accurately determined.
[0047] The fiber-reinforced composite material with strain-damage self-sensing and the preparation method thereof of the present invention can extend the service life of the resin-based composite material, and give the material intelligent self-healing functionality, thereby increasing the healing reaction rate, selecting the self-repair area, and shortening the maintenance cycle. At the same time, the preparation conditions are mild, the process is simple, the economy is good, and the application range is wide. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is a flow chart of the present invention.
[0049] Figure 2 It is a mechanism diagram of uniform dispersion of carboxylated multi-walled carbon nanotubes and their modified fibers of the present invention.
[0050] Figure 3 It is a mechanism diagram showing that the fiber-reinforced composite material of the present invention has a self-sensing function. DETAILED DESCRIPTION
[0051] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0052] Example 1
[0053] This embodiment provides a fiber-reinforced composite material with strain-damage self-sensing, comprising the following raw material components in parts by weight:
[0054] 0.1 dopamine;
[0055] 0.1 parts of carboxylated multi-walled carbon nanotubes;
[0056] 3 parts of nano titanium dioxide;
[0057] 20 parts of acetone;
[0058] 20 parts of anhydrous ethanol;
[0059] 80 parts of deionized water;
[0060] 1 part polyethylene glycol;
[0061] 0.1 parts of ammonia water;
[0062] 0.1 parts of polyvinylpyrrolidone;
[0063] 1 part silane coupling agent;
[0064] 60 unidirectional fiber cloth;
[0065] 1 part polycaprolactone (thermoplastic toughening agent);
[0066] 100 parts of epoxy resin and the corresponding amount of curing agent.
[0067] Example 2
[0068] This embodiment provides a strain-damage self-sensing fiber-reinforced composite material, comprising the following raw material components in parts by weight:
[0069] 0.5 parts dopamine;
[0070] 1 part carboxylated multi-walled carbon nanotubes;
[0071] 5 parts of nano titanium dioxide;
[0072] 60 parts of acetone;
[0073] 80 parts of anhydrous ethanol;
[0074] 120 parts of deionized water;
[0075] 10 parts of polyethylene glycol;
[0076] 2 parts ammonia;
[0077] 1 part polyvinylpyrrolidone;
[0078] 3 parts of silane coupling agent;
[0079] 80 unidirectional fiber cloth;
[0080] 5 parts of polycaprolactone (thermoplastic toughening agent);
[0081] 100 parts of epoxy resin and the corresponding amount of curing agent.
[0082] Example 3
[0083] This embodiment provides a strain-damage self-sensing fiber-reinforced composite material and a preparation method thereof, such as Figure 1 As shown, the following steps are included:
[0084] Step S1: Surface activation modification of carbon fiber based on dopamine;
[0085] Step S2: preparing an epoxy resin intelligent system with damage self-sensing function;
[0086] Step S3: Design of fiber-reinforced composite material with strain-damage self-sensing functional characteristics.
[0087] The invention comprises the following raw material components in parts by weight:
[0088] 0.3 parts dopamine;
[0089] 0.5 parts of carboxylated multi-walled carbon nanotubes;
[0090] 4 parts of nano titanium dioxide;
[0091] 40 parts of acetone;
[0092] 60 parts of anhydrous ethanol;
[0093] 100 parts deionized water;
[0094] 5 parts polyethylene glycol;
[0095] 1 part ammonia;
[0096] 0.5 parts of polyvinylpyrrolidone;
[0097] 2 parts of silane coupling agent;
[0098] 70 parts unidirectional fiber cloth;
[0099] 2.5 parts of polycaprolactone (thermoplastic toughening agent);
[0100] 100 parts of epoxy resin and the corresponding amount of curing agent.
[0101] Further, in step S1, the surface activation modification of carbon fiber based on dopamine includes:
[0102] A mixed solution of ethanol and deionized water was prepared in a formula amount, and ammonia water was added dropwise, and a magnetic stirrer was used to stir evenly to obtain a mixed solution A. Dopamine and polyethylene glycol were added to the deionized water in a formula amount in sequence, and after stirring evenly, they were added to the mixed solution A respectively, and stirred evenly at room temperature with a magnetic stirrer to obtain a mixed solution B. The fiber cloth was placed in the 60°C mixed solution B until the fiber surface was evenly covered. After impregnation, the fiber cloth was taken out and dried for use.
[0103] Furthermore, in step S2, an epoxy resin intelligent system with damage self-sensing function is prepared, comprising:
[0104] Add the formulated amount of polycaprolactone to the formulated amount of acetone, heat and stir at 40°C for 30 minutes until it is completely dissolved, then add the formulated amount of titanium dioxide to it, ultrasonicate and stir for 30 minutes to obtain solution I. In the second step, add the formulated amount of carboxylated multi-walled carbon nanotubes, silane coupling agent and polyvinylpyrrolidone to the anhydrous ethanol solution to obtain solution II. In the third step, then add solution I to the above solution II, stir for 45 minutes to obtain solution III, then add solution III to the formulated amount of epoxy resin, stir at high speed mechanical shear until uniform to obtain solution IV, then put solution IV into a 100°C oil bath pot and heat and stir for 5 hours until the solvent evaporates to obtain solution V, add the formulated amount of curing agent to obtain the epoxy resin intelligent system VI with damage self-sensing function.
[0105] Furthermore, in step S3, the fiber reinforced composite material having strain-damage self-sensing functional characteristics is designed, including:
[0106] The uniformly dispersed solution VI and the modified carbon fiber cloth were vacuum infused to obtain a carbon fiber reinforced composite plate with strain-damage self-sensing functional characteristics, and cured in an oven at 60°C for 48 hours. The cured composite plate was cut into sizes of 50mm×25mm×1.5mm and 12mm×4mm×1.5mm, and three-point bending and short beam shear tests were performed according to ASTMF2344 and ASTM D7264 standards, respectively.
[0107] like Figure 3 As shown, Figure 3 In the figure, a represents the fiber surface treatment; b represents the fiber-resin interface regulation; c represents the resin matrix regulation; and d represents the internal damage (fiber debonding and resin cracking) leading to increased resistance - damage self-sensing mechanism.
[0108] Further, such as Figure 2 As shown, the multi-walled carbon nanotubes are hydroxylated carbon nanotubes with a diameter of 30 nanometers and a length of 30 micrometers; the nano-titanium dioxide particle size is 60 nanometers. At the same time, the solution III is a suspension that has been evenly dispersed in ethanol, and its dispersion mechanism is that the silicon in the silane coupling agent forms a silicon-oxygen covalent bond with the oxygen in the hydroxylated carbon nanotubes. At the same time, the amino group in the silane coupling agent dehydrogenates / water with the hydroxyl or carboxyl group on the surface of the pretreated fiber to form NO or NC covalent bonds, thereby improving the surface activity, mechanical properties and roughness of the fiber.
[0109] Example 4
[0110] This embodiment provides a strain-damage self-sensing fiber-reinforced composite material and a preparation method thereof, such as Figure 1As shown, step S1 and step S2 are the same as those in Example 3; in step S3 of this embodiment, 50% of the ultimate bending strength and 50% of the ultimate short beam shear strength are selected to apply the load, and then the sample is placed in an oven at 80°C for 2 hours, and then the bending and short beam tests are performed.
[0111] Example 5
[0112] This embodiment provides a strain-damage self-sensing fiber-reinforced composite material and a preparation method thereof, such as Figure 1 As shown, step S1 and step S2 are the same as those in Example 3; in step S3 of this embodiment, 70% of the ultimate bending strength and 70% of the ultimate short beam shear strength are selected to apply the load, and then the sample is placed in an oven at 80° C. for 2 hours, and then the bending and short beam tests are performed.
[0113] Example 6
[0114] This embodiment provides a strain-damage self-sensing fiber-reinforced composite material and a preparation method thereof, such as Figure 1 As shown, step S1 and step S2 are the same as those in Example 3; in step S3 of this embodiment, 90% of the ultimate bending strength and 90% of the ultimate short beam shear strength are selected to apply the load, and then the sample is placed in an oven at 80° C. for 2 hours, and then the bending and short beam tests are performed.
[0115] Comparative Example 1
[0116] Vacuum infused carbon fiber reinforced epoxy resin composite (CFRP) plates without any additive reinforcement modification were directly selected for three-point bending and short beam shear tests.
[0117] Comparative Example 2
[0118] The three-point bending and short beam shear specimens in Example 3 were selected for testing after damage treatment.
[0119] Comparative Example 3
[0120] The three-point bending and short beam shear specimens in Example 3 were selected, and the specimens were damaged by the same method as in Example 4 before testing.
[0121] Comparative Example 4
[0122] The three-point bending and short beam shear specimens in Example 3 were selected, and the specimens were damaged by the same method as in Example 5 before testing.
[0123] Comparative Example 5
[0124] The three-point bending and short beam shear specimens in Example 3 were selected, and the specimens were damaged by the same method as in Example 6 before testing.
[0125] Table 1 is the three-point bending performance and short beam shear performance of embodiment 1-6 and comparative example 1-5 carbon fiber reinforced epoxy resin-based composite material before and after damage and self-perception healing, wherein embodiment 3-6 is the same as comparative example 2-5 performance, so embodiment 3-6 is omitted in the table. It can be seen from the table that the reinforcing phase multi-walled carbon nanotubes (MWCNT) and polycaprolactone (PCL) contribute to the mechanical properties of the enhanced composite material, such as embodiment 1 / 2 and comparative example 1 comparison; but the reinforcing phase (MWCNT, PCL) of too much content can not play a role of continuous enhancement, such as can be known by embodiment 2 and comparative example 2 comparison, this is because the addition of too much reinforcing phase can cause filler to agglomerate and cause local stress concentration, which contributes to the initiation and expansion of cracks inside the composite material. Therefore, it is finally determined that the optimal addition amount of multi-walled carbon nanotubes (MWCNT) and polycaprolactone (PCL) is 0.5 parts and 2.5 parts, i.e. comparative example 2. In addition, it can be seen from comparative examples 3-5 that as the percentage of applied limit bending and short beam load increases (from 50% to 70%), the bending strength of the self-sensing healing composite material is restored. At the same time, Table 2 shows the electrical properties of carbon fiber reinforced epoxy resin-based composite materials before and after additive modification and before and after damage sensing healing. It is worth emphasizing that the conductivity of the fiber-reinforced composite material has a consistent change law with strain, and the sensitivity of damage self-sensing can be accurately determined by resistance changes.
[0126] Table 1 Mechanical properties of carbon fiber reinforced epoxy resin composites before and after additive modification and before and after damage sensing healing
[0127]
[0128] Table 2 Electrical properties of carbon fiber reinforced epoxy resin composites before and after additive modification and before and after damage sensing healing
[0129]
[0130] In summary, the fiber-reinforced composite material with strain-damage self-sensing and the preparation method thereof of the present invention can extend the service life of the resin-based composite material, and give the material intelligent self-healing functionality, thereby increasing the healing reaction rate, selecting the self-sensing area, and shortening the maintenance cycle. At the same time, the preparation conditions are mild, the process is simple, the economy is good, and the application range is wide.
[0131] The above implementation cases are only preferred embodiments of the present invention and are not intended to limit the present invention in any form. Although the present invention has been disclosed as above with preferred embodiments, they are not intended to limit the present invention. Therefore, any simple modification, equivalent changes and modifications made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection of the technical solution of the present invention.
Claims
1. A fiber-reinforced composite material with strain-damage self-sensing, characterized in that: The raw material components include the following parts by weight: 0.1-0.5 parts dopamine; 0.1 to 1 part of carboxylated multi-walled carbon nanotubes; 3-5 parts of nano titanium dioxide; 20-60 parts of acetone; 20-80 parts of anhydrous ethanol; 80-120 parts of deionized water; 1-10 parts of polyethylene glycol; 0.1-2 parts of ammonia water; 0.1-1 part of polyvinyl pyrrolidone; 1 to 3 parts of silane coupling agent; 60-80 parts of unidirectional fiber cloth; 1-5 parts of polycaprolactone; 80-120 parts of epoxy resin and corresponding amount of curing agent.
2. The fiber-reinforced composite material with strain-damage self-sensing according to claim 1, characterized in that: The reinforcing fiber is one of carbon fiber, glass fiber, basalt fiber and plant fiber.
3. The fiber-reinforced composite material with strain-damage self-sensing according to claim 2, characterized in that: The carbon fiber is pretreated before use, wherein the pretreatment includes first performing a desizing treatment and then performing an acidification treatment on the desizing carbon fiber.
4. The fiber-reinforced composite material with strain-damage self-sensing and the preparation method thereof according to claim 2, characterized in that: The basalt fiber is pretreated before use, and the pretreatment is first plasma oxidation treatment to carboxylate or hydroxylate the fiber surface.
5. The fiber-reinforced composite material with strain-damage self-sensing according to claim 1, characterized in that: The hydroxylated carbon nanotube has a diameter of 8 nanometers to 50 nanometers and a length of 10 micrometers to 50 micrometers.
6. The fiber-reinforced composite material with strain-damage self-sensing according to claim 1, characterized in that: The particle size of the nano titanium dioxide is 30-100 nanometers.
7. A method for preparing a fiber-reinforced composite material with strain-damage self-sensing, characterized in that: For preparing the composite material according to any one of claims 1 to 6, the preparation method comprises the following steps: Step S1: Surface activation modification of carbon fiber based on dopamine; Prepare a mixed solution of ethanol and deionized water, add different volumes of ammonia water dropwise, and stir evenly to obtain a mixed solution A; add dopamine and polyethylene glycol to the deionized water in sequence, stir evenly, then add to the mixed solution A, and stir evenly at room temperature to obtain a mixed solution B; place the fiber cloth in the mixed solution B at 60°C until the fiber surface is evenly covered, take out the fiber cloth after immersion, and dry it for standby use; Step S2: preparing an epoxy resin solution having damage self-sensing function; The following steps are involved: S2-1, adding polycaprolactone to acetone, heating and stirring at a temperature of 30-50°C for 20-40 minutes to dissolve, then adding nano titanium dioxide, stirring for 20-40 minutes to obtain solution I; The polycaprolactone is incorporated into the resin matrix as a low-melting-point thermoplastic small molecule, and after heating and melting, the melt diffuses into the crack area to fill the internal pores and other defects of the epoxy resin, thereby improving the fracture toughness of the resin system; in addition, the molecular chains of the thermoplastic polycaprolactone melt will be entangled with each other at the thermal activation temperature, and bonded with the resin matrix, showing good interface adhesion; S2-2, adding carboxylated multi-walled carbon nanotubes, silane coupling agent and polyvinylpyrrolidone into anhydrous ethanol solution to obtain solution II; S2-3, adding solution I to solution II, stirring for 30-60 minutes to obtain solution III, then adding solution III to epoxy resin, stirring evenly to obtain solution IV, then placing solution IV in an 80-120°C oil bath, heating and stirring for 4-6 hours until the solvent evaporates to obtain solution V, and then adding a curing agent to obtain epoxy resin solution VI with damage self-sensing function; The solution III is a suspension uniformly dispersed in ethanol, and its dispersion mechanism is that the silicon in the silane coupling agent forms a silicon-oxygen covalent bond with the oxygen in the hydroxylated carbon nanotubes; at the same time, the amino group in the silane coupling agent dehydrogenates / waters with the hydroxyl or carboxyl group on the surface of the pretreated fiber to form a NO or NC covalent bond, thereby improving the surface activity, mechanical properties and roughness of the fiber; Step S3: designing a fiber-reinforced composite material with strain-damage self-sensing; The epoxy resin solution VI of step S2 and the fiber cloth modified in step S1 are subjected to a vacuum infusion process to prepare a fiber reinforced composite material plate having strain-damage self-sensing functional characteristics, and then cured in an oven at 60° C. for 48 hours.
Citation Information
Patent Citations
Preparation method of basalt fiber composite material with damage self-sensing capability
CN116515274B
Cited By
Preparation method of basalt fiber-containing epoxy resin composite board for automobile
CN121064603A